Improving the breeding, cultivation and use of sweetpotato in Africa - Abidin, P.E.; Carey, E.E. (Burleigh Dodds Science Publishing Limited, 2018)
Sweetpotato is a low-input crop with significant potential for improving public health and nutrition and developing food security in sub-Saharan Africa. This chapter examines the nutritional contribution made by OFSP (orange-fleshed sweetpotato) in poor rural communities in Malawi, Ghana, Nigeria and Burkina Faso; sustainable breeding and seed systems; and effective commercialisation and marketing to benefit the communities concerned. The chapter includes detailed case studies from Ghana and Malawi and offers suggestions for future trends for research in this area.